AI Driven Support Networks for Reducing Emotional Isolation Among Infertile Couples - Faridah, Ida; Astrieta, Dhea Ayunanda; Juliastuti, Dyah; Anggraini, Lita; Pokkali, Krishna Chaitanya; Asri, Asri (Pandawan Sejahtera Indonesia, 2025)
Infertility is a global health issue that often leads to social stigma and emotional isolation, profoundly affecting the well-being of individuals and couples. This study explores the role of AI-driven support networks in alleviating these challenges by providing accessible, anonymous, and personalized emotional support. Utilizing a mixed-methods approach, data was collected through surveys and interviews with infertile couples, alongside an analysis of existing AI mental health platforms. The findings reveal significant reductions in stress, anxiety, and depression levels among participants, with anonymity and scalability being the most valued features of these platforms. This study underscores the transformative potential of AI in bridging the gaps in traditional support systems, offering a scalable and inclusive solution for mental health care. The implications for healthcare providers, technology developers, and infertile couples are profound, paving the way for innovative approaches to addressing stigma and emotional well-being.